2008
DOI: 10.1128/jvi.00227-08
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus Vector Can Be Readministered to Nasal Epithelia without Blocking Immune Responses

Abstract: For many envisioned applications of lentivirus vectors as tools in respiratory biology and therapeutic gene delivery, the efficiency of gene transfer must be improved. We previously demonstrated stable, persistent (>11 months) in vivo expression following a single application of a feline immunodeficiency virus (FIV)-based lentivirus vector (GP64-FIV) to murine nasal epithelia. Here we investigate the efficacy of repeated administration of lentivirus vectors to the airways. Using quantitative bioluminescent ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 46 publications
10
95
2
Order By: Relevance
“…AdV, FIV, etc). 14,20 Finally, the lower levels of gene expression we observe on the nasal septum compared to the lateral ciliated regions are consistent with the differences in fluid retention in these two regions. The ability to observe where the dose is retained, or the tissue-type targeted, 21 should be useful in the testing of pharmaceuticals, infectious agents, allergens and other gene vectors in these different epithelial tissues.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…AdV, FIV, etc). 14,20 Finally, the lower levels of gene expression we observe on the nasal septum compared to the lateral ciliated regions are consistent with the differences in fluid retention in these two regions. The ability to observe where the dose is retained, or the tissue-type targeted, 21 should be useful in the testing of pharmaceuticals, infectious agents, allergens and other gene vectors in these different epithelial tissues.…”
Section: Discussionsupporting
confidence: 69%
“…This method now enables the rational design of more effective delivery procedures in the airway gene transfer protocols used in normal and CF mouse models. 1,2,14,15 It should also permit improvements in reliability and repeatability to boost outcome effectiveness, reduce outcome variability, and decrease the volumes of costly gene vectors needed in mouse model studies.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that repeated administration of lentiviral vectors to the mouse nasal epithelium is feasible (10,11). To move our translational research a step closer to clinical relevance we now assessed repeat administration of the vector in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have attempted to further improve lentiviral vector uptake into airway epithelium by changing the viral envelope proteins. Glycoproteins from Ebola or Marburg virus that naturally transfect airway epithelial cells by the apical membrane showed early promise (8), but have more recently been superseded by viral vectors pseudotyped with the influenza M2 envelope glycoprotein (9), baculovirus protein GP64 (10), or the SeV-derived F and HN envelope proteins (11,12).…”
mentioning
confidence: 99%
“…The strategy of ''pseudotyping'' or substitution of the lentivirus envelope with the envelope protein of another virus, such as Ebola virus (Kobinger et al, 2003), baculovirus (Sinn et al, 2008) or Sendai virus (Mitomo et al, 2010) have demonstrated increase in gene transfer efficiency to the airway epithelium. Before the application of lentiviral vectors for pulmonary gene transfer, preclinical studies in large animal models will need to be carried out to carefully assess their efficacy and safety.…”
Section: Integrative Vectorsmentioning
confidence: 99%